Population genetics and phylogenetic placement of the endangered Knysna seahorse, Hippocampus capensis - Teske, Peter R. (Peter Rodja) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2003.